MANAGING HUMAN RESOURCE MANAGEMENT IN BALANCING WORK AND CAREER DEVELOPMENT AT THE KEDIRI DISTRICT SOCIAL SERVICE - Pembayuningtyas, Mimin; Septa Wihara, Dhiyan (JURNAL EKBIS, 2024)
Human Resource Management is the process of resolving every problem in the life of a worker, customer, supplier, manager, and other areas related to workers. Work-life balance is caused by employees' efforts to manage stress, anxiety, and various psychological problems. Career development is supported by business ventures so that the business can continue to grow in the future. This research aims to understand Human Resources Management in balancing work and career development at the Kediri Regency Social Service. Qualitative analysis is in line with descriptive technique, conducting research that has a clear object, and primary data as a summary in the analysis that is used to help the conversation and come directly. Work balance, at its purest, fosters a state in which employees who help manage their time are effective at structuring their time and harmoniously linking work-related demands with personal needs or group responsibilities. Someone who successfully maintains or implements work. work-life balance is an employee with high productivity from a high level of career development. Within the Kediri Regency Social Service there has been a good work ethic and career growth that is in accordance with employee competencies.